(untitled) (African Journal of Biomedical Research, 2019)
Although endogenous Carbon monoxide (CO) is beneficial, exogenous CO exposure may cause increased oxidative stress in other organs. Here, we investigated the effect of sub-chronic exposure of mice to CO from three common sources (cigarette, mosquito coil, and generator) on the brain. 32 mice, weighing 20 – 25g were recruited into one of the four groups. Each group was exposed to either of the 3 smokes for 15 minutes, daily, over 14 days. Digital CO meter was used to measure the amount of CO in the gas chamber (75 cm x 50 cm x 50 cm). Malondialdehyde, glutathione levels and superoxide dismutase activity were measured in the brain. Exposure to generator fumes produces the highest CO (1000 ppm), followed by cigarette smoke (356 ppm) and then MC smoke (304 ppm). Mice that were exposed to the generator fumes had a relatively higher level of MDA (0.04 ɲMol/mL), however, it is not significantly different from that of other groups. There was significant oxidative stress in the cigarette group due to the high SOD activity (2.36 μ/mgprotein) and also in the MC group due to the low GSH level (132.34 mg GSH/ gprotein). The significant oxidative stress observed in the cigarette and MC groups couldn’t have been due to CO alone, some specific constituents of cigarette and MC could have aggravated the problem. Brief, daily exposure to CO from the 3 sources for 14 days was associated with significant oxidative stress that could affect the normal functions of the brain.